Nutritional NUTRITIONAL STATUS WITH PHYSICAL ACTIVITY - Sari, Etika Purnama (Jurnal Ilmiah Kesehatan, 2019)
Malnutrition cause disturbance of processes such as production energy and growth on children. Chidren with age 6-12 years old prefer to watch television. They spend their time more than one hour to watching television and playing a game. The situation caused reducing energy, so can cause overweight.  The purpose of this study was analized the correlation of nutritional status with physical activity. The method of this study used analytic with cross sectional approach. The sampel of this research were 6th grade students at SDN banyu Urip III Surabaya which amounts to 35 students. The sampling technique was simple random sampling. Physical activity was measured with questionnaire and nutritional status used body weight according to age curve from NCHS. The statistic used spearman rho correlation test. The result showed that p value = 0,00 with ?=0,05. It means there is a correlation of nutritional status with physical activity. That situation described about the lack of nutritional status can cause lack of production energy so can cause less agile physical activity and look weak. The recommendation from this study are increasing physical activities beyond study time and increasing the variation of the menu in canteen, so that students can choose nutritious food.